2020
DOI: 10.1530/rep-19-0419
|View full text |Cite
|
Sign up to set email alerts
|

Pre-ovulatory intercellular regulation of miR-125a-3p within mouse ovarian follicles

Abstract: miR-125a-3p, a post-transcription regulator of Fyn kinase, is expressed in mouse pre-ovulatory follicles; its expression within the follicle decreases toward ovulation. Our aim was to follow the synthesis of miR-125a-3p and regulation of its expression in all follicular compartments, focusing on intercellular communication. Mural granulosa cells (GCs) or cumulus cells (CCs) were transfected with either scrambled-miR (negative control) or miR-125a-3p mimic. Freshly isolated GCs or CCs were incubated overnight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…miR-503, for instance, is a potent ovarian microRNA with crucial functions in follicle formation, maturation, and the luteinization process [44][45][46]. Similar reproductive connections are noted for miR-181b, with its strong involvement in the sexual reproduction of boars [47][48][49], and miR-125a with differential expression levels from oogenesis to ovulation in mice [50], indicating their potential roles in fatty acid-induced reproductive dysfunction outside the scope of our experimental paradigm.…”
Section: Discussionmentioning
confidence: 67%
“…miR-503, for instance, is a potent ovarian microRNA with crucial functions in follicle formation, maturation, and the luteinization process [44][45][46]. Similar reproductive connections are noted for miR-181b, with its strong involvement in the sexual reproduction of boars [47][48][49], and miR-125a with differential expression levels from oogenesis to ovulation in mice [50], indicating their potential roles in fatty acid-induced reproductive dysfunction outside the scope of our experimental paradigm.…”
Section: Discussionmentioning
confidence: 67%
“…Both are members of the mir-10 family and were detected in human FF microvesicles [ 56 ]. A recent study demonstrated that miR-125a can be transcribed by all follicular components and play a role in intercellular communication within the follicle [ 59 ]. In mice, miR-125a and miR-125b were highly expressed in GV compared to MII oocytes, and it was also found that they play an important role in regulating maternal genes and zygotic genome activation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%